2019
DOI: 10.1136/jclinpath-2019-206078
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, behaviour and role of biomarkers in metastatic triple-negative breast cancer

Abstract: AimsCharacterising the factors responsible for metastatic triple-negative breast cancer (TNBC) is of significant importance, considering its high mortality rate and scant data. In this study, we evaluated the characteristics, clinical behaviour and role of biomarkers (androgen receptor (AR), oestrogen receptor beta (ERβ) and p53) in metastatic TNBC.MethodsImmunohistochemistry was performed for AR, ERβ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…2 At present, the 5-year survival rate of TNBC is less than 30%. 3 In recent years transcriptional profiling has been used to classify breast cancers into at least five molecular subtypes (basal, claudin-low, luminal A, luminal B, and HER2-enriched). 4 TNBC was mainly composed of basal-like breast cancer (BLBC, 39-54%) and CLBC (25-39%).…”
Section: Introductionmentioning
confidence: 99%
“…2 At present, the 5-year survival rate of TNBC is less than 30%. 3 In recent years transcriptional profiling has been used to classify breast cancers into at least five molecular subtypes (basal, claudin-low, luminal A, luminal B, and HER2-enriched). 4 TNBC was mainly composed of basal-like breast cancer (BLBC, 39-54%) and CLBC (25-39%).…”
Section: Introductionmentioning
confidence: 99%
“…Its gene product “p53” protein showed 90% missense mutation from CpG sites that span 190 diverse codons in the TP53 gene exon that code the DNA-binding region of the p53 protein [ 68 ]. As a result, p53 losses its function, no or poor DNA binding, and restricted transcription [ 69 , 72 , 73 ] caused enhancement in tumour-infiltrating lymphocytes in the stroma [ 73 ], epithelial-mesenchymal transition, high rate of tumorigenesis, cellular invasion/migration, drug resistance, rapid cell division in TNBC cell lines [ 74 , 75 ], and large-sized tumour growth in females [ 76 ]. Similarly, the R330 frame-shift mutation in the coding region at the C-terminus of the GATA3 gene leads to variations in epithelial to mesenchymal tissues causing overexpression and abnormal regulation of breast cell growth and progression.…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%
“…Despite the controversy regarding the correlation between the expression of AR and ER-β in TNBC, it is important to remember that ER-β is co-expressed with AR and may play a suppressive role in a subset of TNBC such as LAR tumors or apocrine carcinomas, suggesting the need for their combined consideration in the treatment of these tumors. Goto et al examined the combined expression of AR, ER-β, and P53 in metastatic TNBC, and showed that AR-/ER-β+/P53+ was significantly correlated with a poorer outcome [ 113 ].…”
Section: The Role Of Each Sex Steroid Hormone In Tnbc In a Clinical Settingmentioning
confidence: 99%